Problems of monetary policy in a developing economy - Khatkhate, Deena R. (Bombay : Co-operators' Book Depot, 1954)
The present book is an attempt to trace in some detail the facts which necessitate a revision in monetary theories and the line on which the corresponding monetary policy must be revised
Bibliographical footnotes.
osc 01/02/2019
Loans
Keywords: Currency question